2014
DOI: 10.1002/j.1556-6676.2014.00127.x
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Dialectical Behavior Therapy for Treating Eating Disorders

Abstract: This study evaluated the effectiveness of dialectical behavior therapy (DBT) for treating eating disorder episodes and co‐occurring depression symptoms among individuals diagnosed with eating disorders. Separate meta‐analytic procedures for between‐groups and single‐group studies were conducted and yielded large effect sizes, indicating that DBT may be efficacious for decreasing disordered episodes among women diagnosed with eating disorders; medium to large effect sizes were noted for treating depression symp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
19
0
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 42 publications
(22 citation statements)
references
References 44 publications
1
19
0
2
Order By: Relevance
“…30 Indeed, meta-analytic work supports DBT as effective in decreasing disordered eating. 31 Should changes in negative urgency precede recovery, it may be that negative urgency serves as a mediator for treatment such as DBT and eating disorder outcomes/recovery.…”
Section: Discussionmentioning
confidence: 99%
“…30 Indeed, meta-analytic work supports DBT as effective in decreasing disordered eating. 31 Should changes in negative urgency precede recovery, it may be that negative urgency serves as a mediator for treatment such as DBT and eating disorder outcomes/recovery.…”
Section: Discussionmentioning
confidence: 99%
“…An alternative treatment that has achieved widespread implementation and positive outcomes for patients suffering from an eating disorder is dialectical behaviour therapy (DBT) (Bankoff, Karpel, Forbes, & Pantalone, 2012;Lenz, Taylor, Fleming, & Serman, 2014). DBT is a cognitive behavioural treatment that was originally developed to treat chronically suicidal patients diagnosed with borderline personality disorder (BPD) (Linehan, 1987), and is now recognized as the leading psychological treatment for this population (National Guideline Clearinghouse, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Research has shown that DBT is effective in treating a wide range of disorders, such as substance dependence (Linehan, Schmidt, Dimeff, Craft, Kanter, & Comtois, 1999), depression (Harley, Sprich, Safren, Jacobo, & Fava, 2008), post-traumatic stress disorder (Harned, Korslund, & Linehan, 2014), and eating disorders (Federici & Wisniewski, 2013;Lenz, Taylor, Fleming, & Serman, 2014;Lynch et al, 2013;Masson, von Ranson, Wallace, & Safer, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…A broader definition of mindfulness treatments includes non-meditative approaches to regulate emotions, as well as strengthen distress tolerance and compassion for oneself and others. Such non-mediative mindfulness interventions have been found to positively impact the outcomes in eating disorder treatments [56]. Adults with high dispositional ("trait") mindfulness appear to display lower levels of ED symptoms compared to those with lower dispositional mindfulness [57].…”
Section: Discussionmentioning
confidence: 99%